Contemporary Issues on Cash Waqf: A Thematic Literature Review - Aldeen, Khaled Nour; Ratih, Inayah Swasti; Herianingrum, Sri (Universitas Muhammadiyah Yogyakarta, 2020)
This paper presents the most recent works on cash Waqf, focusing on identifying contemporary scholars' work in this area, providing a novel framework to indicate the existing gap, subsequently, it opens the door wider for new research commitment. This research adopts the paradigm of qualitative approach research, based on disk-based research. Google Scholar was employed, searching through the passage. Only contemporary English documents within the period of 2002-2019 were the subject of this study. Lately, cash Waqf has been proven as a proper method for poverty alleviation. Previous studies attempted to address several models in order to enhance socio-economics issues. This research is a distinct attempt, as to the best of our knowledge, there is no previous research addressed the subject matter. Moreover, this study is expected to assist the interested scholars by offering comprehensive conclusion about have been done in the field. Hence, opens new doors for scholars to develop new innovative cash Waqf models to bridge the socio-economic issues. Our findings depict that Malaysian and Indonesian scholars show a robust research commitment on cash Waqf during 2002-2019. Furthermore, this study highlights the existing gap that must be researched to enrich the potentials of cash Waqf, future research should address other countries practices in term of cash Waqf, moreover, validating a proposed model through interviews to ensure that a proposed model is applicable. In terms of cash Waqf awareness, research might consider peer influenceâ€, â€œself-efficacy in contributing to cash Waqf.